Design Simulation of Multiple Differential Transceiver at 2.0 GHz for Third Generation Mobile Communication System - Johal, M. S.; Othman,, A. R.; Suaidi, M. K.; Mohd. Dom, H. (2008)
Third generation mobile communication system is widely used nowadays. One of its parameter standard, which is QPSK modulation has been adopted by International Telecommunication Union (ITU) to be used in IMT-2000. However, due to amplitude variations introduced in QPSK, a rather robust and reliable data modulation technique, namely the 7c/4-shift Differential QPSK is proposed. For detection purposes, two types of detectors are evaluated for their performance in AWGN and Rayleigh fading channels. A differential detection technique called multiple differential detection technique which uses maximum-likelihood sequence estimation (MLSE) of the transmitted phases is compared with conventional differential detection which uses symbol-bysymbol detection. By using some of the IMT-2000 standard parameters, the simulation results show that multiple differential detection scheme performs much better than conventional differential detection scheme.